Sistem informasi pemesanan makanan dan minuman berbasis web menggunakan framework codeigniter pada restoran dapoer Bu tutik - Ryzki Apriliani; Yandani, Efri; Asril, Asril (Lembaga Dongan Dosen, 2024)
Abstract− Dapoer Bu Tutik Restaurant is one of the restaurant businesses in the Rimbo Bujang area, Tebo Jambi. Dapoer Bu Tutik Restaurant is a place that provides food and beverage menus to customers according to the specified price. However, at this time, information management still uses a manual system, namely recording orders using a book which results in difficulties in managing orders such as determining who orders food first and the obstacles encountered include frequent errors in writing orders, difficulty in reading customer orders due to handwriting. The purpose of this information system is to process food and beverage ordering data based on the website at Dapoer Bu Tutik Restaurant. This information system is built using the codeigniter framework, a software development method, namely UML (Unified Modeling Language) as a model in system design. The results of this study, researchers can analyze needs, design and build a restaurant and beverage website using codeigniter. The existence of this food and beverage ordering information system can expand marketing and facilitate the process of ordering menus and transactions. Keywords: formation System, Restaurant, Website, Codeigniter, UML